On the Value of Chongqing Back-feeding Agriculture Legislation in China (Global Journal of Human-Social Science, 2012)
The purpose of this study is to find out the value of Chongqing back-feeding agriculture legislation in China by method of literature analysis so as to provide the guidance for establishing the related legislative regulations The purpose value of Chongqing back-feeding agriculture legislation in China is to establish the trial legislation for back-feeding agriculture in China based on the systematical analysis of basic theories institutional arrangement and operational mechanism The moral value of Chongqing back-feeding agriculture legislation in China is to ensure the fairness in entities and procedures and the efficiency in orders and benefits It is concluded that the legislation of Chongqing back-feeding agriculture in China is quite necessary regards to the two type values i e purpose and moral values
Keywords: Back-feeding agriculture; purpose value; moral value; value of legislation